Using PSpice for teaching output current control in d.c.-a.c. inverters to undergraduate students - N. C., Sahoo; R., Vejian; R., Gobbi (MANCHESTER UNIV PRESS, 2008)
In the present day technology of power semiconductor drives, d.c.-a.c. switch-mode voltage source inverters are widely used in a.c. motor servo drives. In these applications, the motor phase currents need to be controlled for high performance. Thus, the prime control issue is to obtain the switching signals for the inverter switches in order to control/regulate the inverter output current. There are various standard ways to derive the switching signals for the inverter. Undergraduate students of electrical engineering should know these basics and get hands-on experience of the inverter current control techniques while taking a course on Power Electronics and Drives. This paper discusses an efficient way of teaching current control in d.c.-a.c. voltage source inverters by computer simulation studies using the student version of PSpice (Release 9.1). Three standard methods have been demonstrated, i.e., triangular carrier method, hysteresis band method, and periodic sampling method. This paper can be used by students for self-study as well as by instructors for simulation-based laboratory experiments.